A call for revamping the policy on import process of anticancer drugs in Pakistan - Elahi, Ehsan; Siddiqui, Adeel (Journal of the Pakistan Medical Association, 2021)
Madam, cancer therapy in Pakistan is a costly treatment financially exhausting patients and their caregivers. Due to the sky high costs of treatment, there is a lack of cancer care facilities in the country. The sale and regulation of anticancer drugs and biologics is controlled by the Drug Regulatory Authority Pakistan (DRAP). DRAP is responsible for granting No Objection Certificate (NOC) to import unregistered drugs either for the patient or the institutional use of a hospital, both subject to renewal. This process can take up from a minimum of 10 days to a maximum of 30 days, for an individual patient it may take up to 1 to 3 days. This was a task almost unachievable before the formation of DRAP. (1,2) In Pakistan, there have been challenges such as price hike in local medicines (3), anticancer drug shortages due to unavailability of active pharmaceutical ingredients (4) as well as COVID19 related raw material and drug availability (5). The average time for importing an unregistered drug from outside the country is about 4-6 weeks, which may be further delayed for months. Our discourse aims to bring attention to this issue, as delay in initiation or continuation of treatment significantly reduces the chances of the patient’s survival with time, which is something they do not have much of We propose the following steps as part of making this process easier for the stakeholders and patients alike: Reduce the time of import of unregistered drugs to 1 week (revamp import process/fast-track) Decentralize authority to provincial DRAP to reduce the burden Once an unregistered drug is imported, it should be registered in the list of special status drugs to fasten future process Facilitate the cancer centers on procurement of import medicines. Hospitals who face inventory challenges- should be able to easily borrow an imported medicine item from a nearby hospital where it is available. Exempt custom duties and taxes on import of such medicines Encourage local manufacturing of generic drugs Abolish regularity duties on import of raw material of said medicines for the manufacturer of such generic drugs Allow multiple sources of drug import Trainee program for DRAP officials dealing with biologics Derive an online process/portal to communicate and update patients and hospitals for delays and implement procedures to deal with such issues (6). Continuous...